Hubungan Harga Diri Dengan Kecemasan Memiliki Pasangan Hidup Pada Perempuan Dewasa Awal - Nisrina Adifa, Balqis; Yuniar Cahyanti, Ika (CV RIFAINSTITUT, 2023)
Anxiety about finding a life partner can be interpreted as a feeling of fear that early adult women experience when they find that they do not yet have a partner. The aim of this research is to determine the relationship between self-esteem and choice of life partner in early adult women. This research was conducted on early adult women aged 18-40 years who did not have a partner or were not married with a total of 49 subjects. Data collection was carried out using a self-esteem scale and an anxiety scale. The data analysis was carried out using the parametric Pearson correlation test using SPSS. From the results of data analysis, a significance value of 0.002 was obtained, which is less than 0.05. And the resulting Pearson Correlation coefficient value is 0.252, which indicates the direction of the correlation is positive. This shows that there is a positive and significant relationship between self-esteem and anxiety. This means that the higher the level of self-esteem, the higher the level of anxiety, and vice versa, the lower the level of self-esteem, the lower the anxiety value.